A comparative study of condyle position in temporomandibular disorder patients with chewing side preference using cone‐beam computed tomography. (11th January 2022) - Ma, Junli; Wang, Jiazhu; Huang, Dongzong; Wang, Zhaowu; Hu, Min; Liu, Hongchen; Jiang, Hua
Abstract: Background: Chewing side preference (CSP) could cause structural and morphological changes of temporomandibular joint (TMJ) and has been suggested as one aetiology of temporomandibular disorders (TMDs), but the condylar position in TMD patients with CSP is unknown. Objective: To compare the condylar position in the TMD patients with and without CSP. Methods: Ninety TMD patients with unilateral symptom (69 with CSP and 21 without CSP) and 20 asymptomatic participants received cone‐beam computed tomography. The condylar position was determined based on the measurements of sagittal joint spaces. Intergroup and intra‐group comparisons of the condylar position were performed. Results: The condyles in asymptomatic participants located nearly randomly in anterior, centric and posterior positions. Patients without CSP had significantly more posterior condyles than asymptomatic participants (57.1% vs 30.0%, p  < 0.05). In patients with CSP, 50.7% of the condyles on the preferred chewing side and 42.0% on the unpreferred side located posteriorly, reaching no significant level compared with the asymptomatic participants and patients without CSP ( p  > 0.05). The symptomatic joints and asymptomatic joints in patients with CSP and without CSP showed no significant differences in condylar position. While patients without CSP had significantly more posterior condyles in symptomatic joints than asymptomatic participants ( p  < 0.05), patients with CSP showed a trend towards more posterior condyles in symptomatic joints compared with the asymptomatic participants (53.6% vs 30.0%, p  = 0.054). Conclusion: Condylar position is not a strong indicator to differentiate CSP‐related TMDs from non‐CSP‐related TMDs. Posterior condyle could not be viewed as one indicator of TMD.